(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Naturally occurring radionuclides in the environment constitute about 85% of public exposure to terrestrial gamma radiation. These radionuclides can be found in sands,clays, soils and rocks, and many ores and minerals, commodities, recycled residues, and other appliances used by humans. There is therefore the need to assess the occurrence of natural radionuclides in Soil Samples from Michika, Adamawa State Nigeria. Forty-six (46) soil samples were collected across different location in Michika, Adamawa State, Nigeria. Gamma ray spectroscopy was used for the analysis. The results obtained show that the mean activity concentration for 226Ra, 232Th and 40K are 81.27, 101.28 and 324.79 Bq/kg respectively. These values are higher than the control value of 35,30 and 35 Bq/kg for 226Ra, 232Th and 40K set by UNSCEAR. The absorbed dose rate (D) ranges from 60.77 to 248.65 nGy/h, which is above the maximum UNSCEAR accepted value of 59nGy/h. The values of total annual effective dose lie between 0.08 and 0.31 mSv y-1 with mean value of 0.14mSv y-1. Also, the mean values of Radium Equivalent Activity were 251.11 Bq/kg. Almost all the value of Raeq were below the maximum recommended value. The mean value of total cancer risk range from 3.28E-6 to 1.3E-5 with mean value of 5.93E-6. All the mean values were above the acceptable range. It can be concluded that the soil is radiologically unsafe for human and animal use. Continuous radiological monitoring of the soil is recommended to safeguard the health of the populace.